A Promising Practice: Using Facebook as a Communication and Social Networking Tool. (December 2013) - Schultz, Susan M.; Jacobs, Gloria; Schultz, Jacob
Individuals with autism often face barriers to social interaction. Residing in a rural environment can compound these difficulties for individuals diagnosed with autism. Some of the reasons include transportation problems and small social networks, in addition to the characteristics of autism. This article discusses a promising practice for supporting the communication and social opportunities for individuals with autism. The authors examined how Facebook supported the social interaction of Jacob, a 28-year old with High Functioning Autism. The findings suggested that, through Facebook, Jacob increased the quantity and quality of social ties he had with others. The authors argue that although online social networking has limitations, with supervision, tools such as Facebook hold potential for developing and increasing social interaction for individuals with High Functioning Autism /Asperger Syndrome.